Greeting the Lunar New Year on Taiwan - Lee, David Tawei; Yu, Kang-ping; Lee, David Tawei (Taiwan : Hanson Production [production company] ; Taiwan : Kwang Hwa Mass Communications [distributors])
The lunar year is like a long red thread that runs through the history of the Chinese people. It passes through thousands of years, links China's two great rivers, crosses the straits of Taiwan and, indeed, extends throughout the world, creating an intricate web throughout time and space that cannot be broken
Copy available in DVD format
Executive producer, Ho Ming-jui, Chang Chia-wei ; script , Chen Li-ping, Lee Yuh-hu ; musical, Huang Shih Chen, Shih-hsing
Narrator: Paul G. Meader
Keywords: Social life and customs